Anchored Ni‐dimethylglyoxime complex on Fe3O4@SiO2 core/shell nanoparticles for the clean catalytical synthesis of dicoumarols. (23rd November 2019) - Hassanloie, Nishtman; Noroozi Pesyan, Nader; Sheykhaghaei, Golaleh
Abstract : Ni‐Dimethylglyoxime complex immobilized on functionalized Fe3 O4 was synthesized by a post‐grafting way and utilized as a novel, thermally stable, recoverable, and efficient for green synthesis of dicoumarols through reaction of 4‐hydroxycoumarin with various aldehydes in excellent yields and higher rate. Fe3 O4 @SiO2 ‐silylcyclopropyl‐dimethylglyoxime‐Ni superparamagnetic nanoparticles (MNPs ) were investigated by Fourier transform infrared spectroscopy, scanning electron microscopy, energy dispersive X‐ray spectroscopy, X‐ray diffraction, vibrating sample magnetometer, and Brunauer–Emmett–Teller technique. This nanocatalyst could be conveniently recovered via the use of an external magnetic field and reused for subsequent reactions for at least 7 times without any remarkable change and decrease in catalytic activity. Abstract : Ni‐Dimethylglyoxime complex immobilized on functionalized Fe3 O4 was synthesized and used for green synthesis of dicoumarols through reaction of 4‐hydroxycoumarin with various aldehydes in excellent yields and higher rate.